Development of a Supply Chain Information System Framework for Sustainable Manufacturing Operations - Magdalena, Lena; Febima, Mesi; Hatta, Muhammad (Proceeding International Conference on Religion, Science and Education, 2026)
The increasing complexity of manufacturing activities requires efficient, integrated, and technology-driven solutions to manage supply chain processes effectively. Supply chain management (SCM) has become a critical component in ensuring competitiveness, agility, and sustainability within manufacturing industries. However, many organizations still face challenges in aligning operational activities with real-time information flow, which often leads to inefficiencies such as delays, excess inventory, and increased operational costs. This study aims to develop a conceptual framework for a Supply Chain Information System (SCIS) that supports manufacturing operations by integrating key supply chain functions into a unified digital platform.The proposed framework is designed to enhance decision-making processes by providing accurate and timely information across procurement, production, inventory, and distribution activities. The development approach combines system design principles with best practices from SCM, emphasizing data integration, process standardization, and digital connectivity. The framework also incorporates performance monitoring mechanisms that allow manufacturers to evaluate operational efficiency and identify areas for continuous improvement.The findings highlight that implementing an SCIS framework can improve collaboration among stakeholders, reduce lead times, optimize resource allocation, and strengthen supply chain visibility. Furthermore, the framework supports manufacturing firms in adapting to dynamic market demands and mitigating risks associated with supply chain disruptions. By leveraging digital technologies, the system ensures real-time data exchange and facilitates predictive analytics for proactive decision-making.In conclusion, this research contributes to both academic and practical perspectives by presenting a structured framework for developing a supply chain information system tailored to manufacturing operations. The study underscores the potential of information system design as a strategic enabler for operational excellence and sustainable manufacturing practices. Future research is recommended to validate the framework through case studies and empirical testing within diverse industrial contexts.